Cysteinyl-leukotrienes promote cutaneous Leishmaniasis control - Noronha, Letícia Paula Trajano; Martins, Monique Daiane Andrade; Castro-Junior, Archimedes Barbosa; Thorstenberg, Maria Luiza; Costa-Soares, Laís; Rangel, Thuany Prado; Carvalho-Gondim, Felipe; Rossi-Bergmann, Bartira; Savio, Luiz Eduardo Baggio; Canetti, Claudio de Azevedo; Coutinho-Silva, Robson (Frontiers in Cellular and Infection Microbiology, 2023)
Leishmaniasis is a neglected tropical parasitic disease with few drugs approved for its treatment. Cutaneous leishmaniasis (CL) is the most frequent form of the disease, responsible for 1.2 million new cases annually worldwide. Mice infected with Leishmania amazonensis are a model of CL infection and drug screening. Leukotrienes are lipid mediators of inflammation produced in response to cell damage or infection. They are subdivided into leukotriene B4 (LTB4) and cysteinyl leukotrienes LTC4 and LTD4 (Cys-LT), depending on the enzyme responsible for their production. Recently, we showed that LTB4 could be a target for purinergic signaling controlling Leishmania amazonensis infection, but the importance of Cys-LT in the resolution of infection remained unknown. Here, we describe that Cys-LT play a role in controlling Leishmania amazonensis infection in susceptible (BALB/c) and resistant (C57BL/6) mouse strains. In vitro, Cys-LT significantly diminished the L. amazonensis infection index in peritoneal macrophages of both BALB/c and C57Bl/6 mice. In vivo, intralesional treatment with Cys-LT reduced the lesion size and parasite loads in the infected footpads of C57Bl/6 mice. The antileishmanial role of Cys-LT was dependent on the purinergic P2X7 receptor, as infected cells lacking the receptor could not produce Cys-LT in response to ATP. In conclusion, our findings indicate the therapeutic potential of not only LTB4, but also Cys-LT for the treatment of CL.